Chyle Leak after Right Axillary Lymph Node Dissection in a Patient with Breast Cancer. (11th February 2021) - Sarawagi, Ankita; Maxwell, Jessica
Abstract : Background . A female patient was diagnosed with a right-sided chyle leak following right skin sparing mastectomy, axillary lymph node dissection, and immediate tissue expander placement in the setting of invasive ductal carcinoma status post neoadjuvant chemotherapy. Summary . Our patient underwent a level I and II right axillary lymph node dissection followed by an axillary drain placement. On the first postoperative day, a change from serosanguinous to milky fluid in this drain was noted. The patient was diagnosed with a chyle leak based on the milky appearance and elevated triglyceride levels in the fluid. While chyle leaks are rare after an axillary dissection and even rarer to present on the right side, it is a complication of which breast surgeons should be aware. The cause of this complication is thought to be due to injury of the main thoracic duct, its branches, the subclavian duct, or its tributaries. Management is usually conservative; however, awareness of this potential complication even on the right side is of the utmost importance Conclusion . Chyle leaks are an uncommon complication of axillary node dissections and even rarer for them to present on the right side. It can be diagnosed by monitoring the drainage for changes in appearance and volume and by conducting supporting laboratory tests. Conservative management is generally suggested.